Support for the Poor in the Mishnaic Law of Agriculture: Tractate Peah - Brooks, Roger (Brown Judaic Studies, 2020)
This study seeks to uncover Tractate Peah's meaning by explaining its laws as they were understood by their authors around 200 C.E. Brooks offers both a new translation of the tractate as well as a commentary and study of it, throwing light on both the individual parts of the Mishnah and the general outlook embedded in the tractate as a whole. The study takes both a diachronic and synchronic approach, allowing us to see how the framers of the Mishnah understood their biblical heritage in light of their own contemporary situation.